Practicum tutorials in initial teacher training: conditions, strategies, and effects of reflective practice - Ruffinelli, Andrea; Hoz, Silvana de la; Álvarez, Carolina (Universidad de los Andes. Facultad de Ciencias Sociales. Departamento de Antropología, 2020)
This paper systematizes the research findings of publications in the last 5-years related to reflective practice in practicum tutorials in initial teacher training, by means of a literature review. The objective is to contribute new knowledge about reflective practice, structuring it around its conditions, development strategies, and effects, considering metacognitive and generative factors, enriching theory about how to teach reflection. The results show there is progress in the field in terms of proposals for different devices and strategies to teach reflective practice in initial teacher training, and emerging findings regarding its effects.
Tutorías de prácticas en la formación inicial del profesorado : condiciones, estrategias y efectos de la práctica reflexiva
Indexado en: Scopus
Factor de Impacto JCR 2024: FI 1,2
Cuartil 2024: Q3
ORCID de Autor/a Ruffinelli, Andrea: 0000-0001-9096-6463
Keywords: Reflective practice; Reflective learning; Practicum tutorials; Initial teacher training; Literature review